Midwifery Care for Pregnant Women with Low Back Pain Discomfort in the Maternity Home: Asuhan Kebidanan Pada Ibu Hamil dengan Ketidaknyaman Low Back Pain di Rumah Bersalin - Tjondro, Lidya Agustin; Hanum, Sri Mukhodim Faridah; Rosyidah, Rafhani (Universitas Muhammadiyah Sidoarjo, 2020)
Third trimester pregnancy is a pregnancy that occurs at a vulnerable gestational age from the 28th to the 40th week. ANC visits to pregnant women aim to improve the quality of life of pregnant women to detect the risk of pregnancy as early as possible in the third trimester. Sometimes there are complaints of physical changes felt by pregnant women, such as lower back pain that causes pregnant women to be disturbed. This case study was conducted at the Eva Candi Sidoarjo Maternity Home and Clinic from 04 to 09 January 2020. Midwifery care was carried out through interviews and documentation using the SOAP method. Midwifery care was implemented and went well without any complications. In the documentation results, there is no discrepancy between the results of the examination and the theory.